2022
DOI: 10.3390/healthcare10101885
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategies and Mental Disorders among the LGBT+ Community in Malaysia

Abstract: The LGBT+ community in Malaysia is vulnerable to mental disorders due to the pressures of being in a conservative heteronormative culture. This study aimed to study the association between coping strategies as well as the sociodemographic factors of LGBT+ individuals with mental disorders and quantify the occurrence of mental disorders among them. This study used a cross-sectional design. The self-rated Brief Coping Orientation to Problem Experienced Inventory (Brief COPE) and the Mini International Neuropsych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The finding reiterates that LGBTQ + perspectives are becoming less pathologic and/or less separated from those considered to be the societal norms than before [ 3 ]. However, there were differences from other Asian nations, such as Malaysia, that there remains a stigma against individuals with LGBTQ + preferences [ 20 ]. Therefore, the different results could be attributed to the nature of the sample, i.e., ethnicity, culture, and individuals with psychiatric illnesses may have different characteristics or attitudes compared to individuals with other illnesses or members of the general population.…”
Section: Discussionmentioning
confidence: 99%
“…The finding reiterates that LGBTQ + perspectives are becoming less pathologic and/or less separated from those considered to be the societal norms than before [ 3 ]. However, there were differences from other Asian nations, such as Malaysia, that there remains a stigma against individuals with LGBTQ + preferences [ 20 ]. Therefore, the different results could be attributed to the nature of the sample, i.e., ethnicity, culture, and individuals with psychiatric illnesses may have different characteristics or attitudes compared to individuals with other illnesses or members of the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other contextual aspects have been considered, for example, Polihronakis et al [33] showed that discrimination in bisexual women has a direct relationship with internalization and sexual risk behaviors, increasing the odds of engaging in it and showing higher rates of STIs and HIV. To understand how discrimination against sexual minorities affects sexual health, more studies need to be conducted to better manage mental disorders in the LGBTQ+ community [57]. Lastly, psychosocial factors influence HSDD and interfere in the relationship with the partner and mental and emotional well-being [30].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other contextual aspects have been considered, for example, Polihronakis et al [33] showed that marginalization has a direct relationship with internalization and sexual risk behaviors. To understand how discrimination against sexual minorities affects sexual health, more studies need to be conducted to better manage the mental disorders of the LGBTQ+ community [57]. Lastly, psychosocial factors influence HSDD, they interfere in the relationship with the partner, and mental and emotional well-being [30].…”
Section: Discussionmentioning
confidence: 99%